Reformulasi Pertanggungjawaban Negara terhadap Kerusakan Lingkungan Lintas Batas dalam Perspektif Ekologi Hukum - Mufti, Muhammad Wildan (Media Hukum Indonesia (MHI), 2026)
Transboundary environmental harm presents a serious challenge in international law because activities conducted by one state may cause significant ecological impacts on another. The current doctrine of state responsibility remains inadequate, primarily due to the dominance of state sovereignty, difficulties in proving causation, weak due diligence standards, and the absence of binding sanctions or ecological restoration mechanisms. This study analyzes these shortcomings and proposes a more ecologically responsive reformulation model through an ecocentric approach and ecological jurisprudence perspective. The proposed reform strengthens the principles of prevention, ecological restoration obligations, cross-border transparency, and more robust enforcement mechanisms. Thus, state responsibility becomes not only compensatory but also oriented toward ecosystem protection and intergenerational justice as the foundation for sustainable global environmental governance.